select the difference of (8x^2-3x^3)-(4x^2-9x^3)

Question|Asked by bjones1988

Asked 11/29/2014 12:47:54 AM

Updated 11/29/2014 4:39:32 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [11/29/2014 4:38:32 AM]

s

heartfairy88|Points 20|

emdjay23|Points 18642|

Question|Asked by bjones1988

Asked 11/29/2014 12:47:54 AM

Updated 11/29/2014 4:39:32 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [11/29/2014 4:38:32 AM]

Rating

8

(8x^2 - 3x^3) - (4x^2 - 9x^3)

= (8x^2 - 3x^3) + (-4x^2 + 9x^3)

= 6x^3 + 4x^2

= (8x^2 - 3x^3) + (-4x^2 + 9x^3)

= 6x^3 + 4x^2

Added 11/29/2014 4:38:31 AM

This answer has been confirmed as correct and helpful.

8

(7x - 2)(5x + 3)

= 35x^2 + 21x - 10x - 6

= 35x^2 + 11x - 6

= 35x^2 + 21x - 10x - 6

= 35x^2 + 11x - 6

Added 11/29/2014 4:39:32 AM

This answer has been confirmed as correct and helpful.

Simplify x^8*x^3*x^7

Question

Not Answered

Updated 11/23/2014 9:10:43 PM

1 Answer/Comment

x^8*x^3*x^7

= x^11*x^7

= x^18

= x^11*x^7

= x^18

Added 11/23/2014 6:04:46 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/23/2014 9:10:34 PM]

34,445,626

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 590 [Total 6463] Ratings 10 Comments 490 Invitations 0 Offline

There are no comments.